2014
DOI: 10.1007/s40616-014-0013-z
|View full text |Cite|
|
Sign up to set email alerts
|

Selection-Based Instruction and the Emergence of Topography-Based Responses to Interview Questions

Abstract: The process of teaching job interview skills to adults with intellectual disability can be time consuming and arduous for vocational developmental centers. On review of the existing literature, Schloss et al. (1988) recognized that although the social validity of interview skills has been well documented, few studies have attempted to validate effective strategies for teaching such behaviors. Behavioral skills training (BST) has been shown to be effective (Hall et al. 1980;Kelly et al. 1980;Schloss et al. 1988… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…The authors concluded that SB instruction for responses to interview questions should include a TB component and that lag reinforcement schedules can be useful in promoting variable responding during SB instruction. Similar to the findings of O’Neill and Rehfeldt (2014), each target question came to evoke multiple accurate responses that were promoted by Lags 1–2 reinforcement schedules.…”
Section: Sb Responding To Interview Questionssupporting
confidence: 55%
See 2 more Smart Citations
“…The authors concluded that SB instruction for responses to interview questions should include a TB component and that lag reinforcement schedules can be useful in promoting variable responding during SB instruction. Similar to the findings of O’Neill and Rehfeldt (2014), each target question came to evoke multiple accurate responses that were promoted by Lags 1–2 reinforcement schedules.…”
Section: Sb Responding To Interview Questionssupporting
confidence: 55%
“…O’Neill and Rehfeldt (2014) suggested that 1 hr of exposure to SB instruction was sufficient to promote varied TB responses in two individuals with a learning disability. A Lag 1 reinforcement schedule was incorporated in order to promote variable SB responses to each of three typical interview questions.…”
Section: Sb Responding To Interview Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dashed line represents the mastery criterion stressing as a great many higher educational classrooms incorporate SB (i.e., multiple choice) examinations, the results of which may not generalize to relevant response topographies. Future investigations might evaluate a technique employed by O'Neill and Rehfeldt (2014) and examined by O'Neill et al (2015) wherein a TB component is included in the procedure by asking participants to read responses aloud during SB instruction.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, multiple studies have demonstrated success with lag schedules of reinforcement on emergent intraverbal responding with children and adults with developmental disabilities (Contreras & Betz, 2016;Lee & Sturmey, 2014;O'Neill, Blowers, & Rehfeldt, 2015: O'Neill & Rehfeldt, 2014, Susa & Schlinger, 2012. For example, O'Neill and Rehfeldt used a lag-1 reinforcement schedule during selection-based training by reinforcing participants' responses when they selected a different response than the last prior response to an interview question presented on a computer screen.…”
Section: Research Emphasismentioning
confidence: 99%